Neurodevelopmental disease genes implicated by de novo mutation and copy number variation morbidity. (January 2019) - Coe, Bradley; Stessman, Holly; Sulovari, Arvis; Geisheker, Madeleine; Bakken, Trygve; Lake, Allison; Dougherty, Joseph; Lein, Ed; Hormozdiari, Fereydoun; Bernier, Raphael; Eichler, Evan
Abstract We combined de novo mutation (DNM) data from 10, 927 individuals with developmental delay and autism to identify 253 candidate neurodevelopmental disease genes with an excess of missense and/or likely gene-disruptive (LGD) mutations. Of these genes, 124 reach exome-wide significance (P < 5 × 10−7 ) for DNM. Intersecting these results with copy number variation (CNV) morbidity data shows an enrichment for genomic disorder regions (30/253, likelihood ratio (LR) +1.85, P = 0.0017). We identify genes with an excess of missense DNMs overlapping deletion syndromes (for example, KIF1A and the 2q37 deletion) as well as duplication syndromes, such as recurrentMAPK3 missense mutations within the chromosome 16p11.2 duplication, recurrentCHD4 missense DNMs in the 12p13 duplication region, and recurrentWDFY4 missense DNMs in the 10q11.23 duplication region. Network analyses of genes showing an excess of DNMs highlights functional networks, including cell-specific enrichments in the D1+ and D2+ spiny neurons of the striatum. Analysis of 10, 000 cases of developmental delay and autism identifies 253 candidate neurodevelopmental disease genes. Network analysis highlights cell-specific enrichments of disease-related genes in the D1+ and D2+ spiny neurons of the striatum.